2022
DOI: 10.3389/fonc.2022.951167
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-1 family in bone metastasis of prostate cancer

Abstract: Prostate cancer (PCa) is one of the most fatal diseases in male patients with high bone metastatic potential. Bone metastasis severely shortens overall survival and brings skeletal-related events (SREs) which reduces the life quality of patients, and this situation is currently regarded as irreversible and incurable. The progression and metastasis of PCa are found to be closely associated with inflammatory cytokines and chemokines. As pivotal members of inflammatory cytokines, Interleukin-1 (IL-1) family plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 113 publications
1
6
0
Order By: Relevance
“…Analogous results were obtained in prostate cancer models, in which the overexpression of IL-1β increased bone metastasis [54,58].…”
Section: Il1 Family In Bone Metastasissupporting
confidence: 71%
See 2 more Smart Citations
“…Analogous results were obtained in prostate cancer models, in which the overexpression of IL-1β increased bone metastasis [54,58].…”
Section: Il1 Family In Bone Metastasissupporting
confidence: 71%
“…Bone metastasis occurs when cancer cells from primary tumors, such as breast, prostate, lung, and bone tumors, or other malignancies, spread to the bone. This process involves a complex interplay of various molecular and cellular factors, and emerging evidence suggests that IL-1 is actively involved in several mechanisms of this metastatic cascade [27,[54][55][56].…”
Section: Il1 Family In Bone Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that progenitors of MAFs become activated when treated with a conditioned medium from tumour cells [ 13 , 43 , 44 ]. Of the myriad of soluble factors identified from the secretome of cancer cells, ligands belonging to the TGF-β superfamily [ 45 , 46 ], platelet-derived growth factors (PDGFs) [ 47 ], inflammatory cytokines, and chemokines such as interleukins (IL) [ 48 ], and more recently, exosomes and macrovesicles [ 49 ] have been implicated in this transformative process. While both PC3 and MDA-Pca 2b cells were originally isolated from bone metastases, their secretome profiles are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-1β plays an important role in the inflammatory cascade by promoting the recruitment of inflammatory cells and increasing the production of other cytokines. These cytokines have a key effect on the progression of bone metastasis and many types of cancers ( 69 ). Multiple pieces of evidence have demonstrated that inflammation can stimulate bone metastasis through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%